Sunflower Seed Husk as Promising By-Product for Soil Biodisinfestation Treatments and Fertility Improvement in Protected Lettuce Crop - Gandariasbeitia, Maite; López-Pérez, José Antonio; Juaristi, Berdaitz; Larregla, Santiago (Frontiers in Sustainable Food Systems, 2022)
One of the major challenges in biodisinfestation treatments against soilborne pathogens is the selection of the proper organic amendments and mixture features. The use of agro-industrial by-products is a sustainable alternative with proven efficacy, but the availability has to be considered in terms of location and quantity. Sunflower seed is one of the five major oil crops widely cultivated and the husk constitutes a significant part that is discarded. This by-product brings together the features to be considered an interesting organic amendment in agricultural soils because of its lignocellulose content, but no references have been found in this field. In this study, sunflower seed husk was used with fresh cow manure in biodisinfestation treatments, alone or combined with other by-products (rapeseed cake, beer bagasse and wheat bran). The assay was performed in summer in a commercial greenhouse with significant yield losses in lettuce crops caused by the root-knot nematode Meloidogyne incognita. Four different amendment mixtures were applied which included 3kg/m2 cow manure, as common waste, and 1 kg/m2 of by-products (dry weight), considering 6mgC/g soil in all treatments but different C/N ratio (23, 29, 31, 34) and by-products. Data was collected in three moments: (i) before and (ii) after biodisinfestation treatments and (iii) after harvesting the first crop after biodisinfestations. Crop damage was assessed through root galling index and the number of eggs in roots. The effects on the pathogen population and the whole soil nematode community were assessed along with some physicochemical and soil microbiological variables (respiration rate, microbial organic C, water-soluble organic C and physiological profile of heterotrophic bacteria through Biolog Ecoplates™). All treatments reported effectiveness in disease control without significant differences among them, but among times. However, soil temperatures during biodisinfestations were higher at higher C/N ratios and fertility variables also increased in these cases, mainly in the treatment with husk as the only by-product. Sunflower seed husk proved to be an interesting source of organic C to improve both biodisinfestation treatments and soil fertility in humid temperate climate zones.